ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN OTOMOTIF DAN KOMPONEN - Petty Aprilia Sari; Imam Hidayat (KRISNA: Kumpulan Riset Akuntansi, 2022)
Return is the return obtained from an investment for a certain period. It will be difficult to know how much return will be obtained in the future. There are many factors to predict return including Total Cash Flow, Accounting Profit, Company Size. This study aims to analyze the effect of total cash flow, accounting profit and company size on stock returns. This type of research is secondary data in the form of annual financial report data for automotive and component companies on the Indonesia Stock Exchange for the 2015-2019 period. Based on the purposive sampling technique, a sample of 9 companies was obtained. The data analysis technique used multiple linear regression. Hypothesis testing was carried out with simultaneous significant test (F-test) and partial test (t-test). The results of this study operating cash flow and accounting profit have an effect on stock returns, while the size of the company has no effect on stock returns. This research can contribute to increase the literature and provide information about the factors that affect stock returns that can be used by companies and investors.